ROOT PRUNING IN Rheedia gardneriana SEEDLINGS - CASTRO FARIA, Álvaro Boson de; HIRANO, Elcio; PORTELA, Osmael; VOSGERAU, Jackson Luiz; NOGUEIRA, Antonio Carlos (Scientia Agraria, 2007)
Seedlings of Rheedia gardneriana 2,5 years old were submitted to root pruning in two ways; drastic root pruning and pruning of taproot with purpose of verify if its way to keep the seedlings for long time in the nursery in order to wait for planting time at definitive field. The experimental design used was fully randomized with 48 plants per treatment. At 70 days after root pruning and transplant to other recipient, it was observed that the mortality rate was 66% for drastic pruning and 68,75% for principal root pruning, while in the control group without root pruning the rate of mortality was 0%. By measurements of canopy dry weight, the results shown difference between the control group with others treatments. The conclusion was that the root pruning is not recommended for seedling to larger pots on this mentioned conditions.